PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.2DI SMP NEGERI 21 KOTA BENGKULU - furwanto, eko; M Fachruddin S, M Fachruddin S; Susanta, Agus (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2018)
This study aims to determine how to implement cooperative learning think pair share (TPS) to be able to enhance the activity and results of students' mathematics learning class VII.2 SMPN 21 Bengkulu City. This type of research is the Classroom Action Research (PTK). Subjects in this study were students of class VII.2 SMPN 21 Bengkulu City totaling 30 students. The instrument used in this study is the observation sheet student activity and achievement test. The results showed that the implementation of cooperative learning type of think pair share (TPS) can increase the activity and student learning outcomes.Increased activity of students can be seen from the average score on the student activity observation sheet first cycle to the third cycle in a row: 15,5 (less criteria inactive); 19,95 (active enough criteria); 24,5 (active criteria).Improving student learning outcomes can be seen from the increase in the average value of students and the percentage of completeness classical study of the first cycle to cycle III respectively: 49.26; 63.46; 76 and 3.3%; 46.6% ; 83.3%.